Under a bad sun : police, politics, and corruption in Australia - Bleakley, Paul (Michigan State University Press, 2021)
"Historical criminologist Paul Bleakley examines a case of police corruption in Queensland, Australia, in which law enforcement had free rein to profit from criminalized vice in return for supporting the government's repression and persecution of its political enemies, from punk music fans to gay men to protestors. While intimidating members of the political opposition, the police also protected the state premier's friends and allies from criminal prosecution-even for offenses as serious as child sex abuse. When journalists and investigators revealed this corrupt bargain in 1987, the premier was forced from office and the police commissioner went to prison"--